Factors Influence Purchase Intention Towards Hairstyling Industry in Bandung - Panigara, Gama; Ratnaningtyas, Sudrajati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Lifestyle is a growing industry in Bandung. Infinity Hair Pomade is a company based in Bandung that creating a business in Lifestyle industry with hairstyling as it’s specifically with target market of males who lived in Bandung with the main consumer aged 15-35 years old. The industry has a great potential and currently dominated by Gatsby with more than 60 percent share in the market. Infinity Hair Pomade which is the new comer currently has no specific strategy to deal with the market leader, but it has a great opportunity to gain a huge market as long as they can get the consumer’s purchase intention and doing a specific strategy to deal with the market leader. This research conducted to see the affect of brand image, pricing, and perceived quality towards the purchase intention in hairstyling industry in Bandung. The total of 100 people becomes the respondents of this research with the criteria of living in Bandung and between 15-35 years old. The data were analyzed using multiple linear regressions since the study using three independent variables and one dependent variable. The findings show that brand image and perceived quality have a significant influence towards purchase intention of hairstyling industry in Bandung, otherwise pricing is not significantly influence the dependent variable. Keywords: purchase intention; brand image; pricing; perceived quality; men’s hairstyling industry